Effects of Drought Stress on Morphological and Physiological Traits of Kochia Prostrata (L.) - Heidari, Fateme; Tilaki, Ghasem Ali Dianati; Kooch, Yahya (International Journal of Natural Sciences Research, 2022)
Drought and desertification have become global environmental problems, posing new obstacles to plant survival and adaptability. The main objective of this study was to evaluate the effect of drought stress on the morphological and physiological traits of Kochia prostrata. (L.) in greenhouse conditions. In the greenhouse experiment, drought stress was conducted in four levels of water regime treatment: 25, 50, 75, and 100 percent field capacity (FC). The experimental design consisted of a completely random design with three replications and 25 seeds per pot for every replication. In the greenhouse, seeds were planted in the soil using plastic containers. Then, 120 days of drought stress were administered, and morphological and physiological parameters were examined. The data were processed, and comparisons of means using the Duncan test (P0.05) were performed. Results demonstrated that when drought stress increased, the morphological and physiological features of K. prostrata decreased significantly. The highest plant dry weight was observed in drought stress of 25% FC and 100% FC with171.45 cm and 282.7 mg, respectively. The lowest rates of photosynthesis, stomatal conductance, transpiration, and mesophyll were observed in 25%FC stress treatments with 0.44 mmol m-1s-1, 0.070 mmol m-1s-1, 1.70 mmol-2s-1, 394.13 respectively. Plant length and Root dry weight are variables that decreased significantly with increasing drought stress. However, the decrease in the values of these variables was not significant at 50, 75, and 100%FClevels but was significant at the most severe drought level (25%FC). Based on the results of this study, it can be suggested that the K. prostrata species can be used in the sustainable development of ecological rehabilitation areas.